Life cycle assessment of in situ mariculture in the Mediterranean Sea for the production of bioactive compounds from the sponge Sarcotragus spinosulus. (20th January 2017) - Pérez-López, Paula; Ledda, Fabio D.; Bisio, Angela; Feijoo, Gumersindo; Perino, Erica; Pronzato, Roberto; Manconi, Renata; Moreira, Maria Teresa
Abstract: Marine sponges are one of the most diverse invertebrates and show a great ability to produce valuable natural products with high biological activities. The main bottleneck for the commercial exploitation is the need of continuous biomass production in sufficient amount. In this study, the in situ cultivation of the sponge Sarcotragus spinosulus in sea-based farming structures was evaluated according to the Life Cycle Assessment (LCA) standardized methodology. The results demonstrated that the cultivation aiming at the extraction of bioactive molecules had a more environmentally-friendly performance than the subsequent downstream processes, which were the main cause of the impact. Moreover, the simulation of alternative scenarios showed the possibility of achieving remarkable reductions of impact and the effect of changes in key issues of the process: the effect of different approaches in the use of boats (exclusively used for the sea-based farming plants and the sponges collection or shared for other activities) as well as the influence of the survival rate. Highlights: A sea-based farming system for in situ sponge cultivation is proposed. Life Cycle Assessment method was applied to evaluate the environmental performance. Downstream processes were identified as the environmental hot spot. The simulated alternative scenarios showed a remarkable improvement potential.